Personal self-heating and cooling food/drink container (using thermoelectric module) - Felix Chandra Kurniawan (2010)
In this Final Year Project, the author explored the application of thermoelectric module (peltier) for a self-heating and self-cooling food/drink container. Peltier is a small solid-state device that acts like a heat pump. When voltage is supplied, heat will be pumped from one side to the other. As a result, peltier has a hot side and a cool side. The author made use of this capability to provide the required heating and cooling within a single product. However, heating and cooling will take place individually and not concurrently. Function analysis diagram, morphological chart and decision matrix were used in the conceptual design stage to select the best design. Calculations were done and selection process was carried out to choose the key components. Four major components in this product are peltier, heat sink, cooling system and power supply. The prototype would then be built using the selected components and tested for both heating and cooling process. Heating experiments were tested on plain rice where the food was expected to be warmed up to 55ºC. On the other hand, cooling experiments were conducted on a canned drink whereby the drink was projected to be cooled down to 10ºC. After the first stage of testing, improvements were made. The newly-improved prototype would be subjected to a final round of testing. For all the experiments, temperature at a certain time interval would be recorded. The author would then analyse all the experimental results to determine if the product has met the requirements. At the end, the author would also suggest possible future developments for this product.